Demon dentist eaudiobook - Walliams, David (Nudged Children's Audiobooks, 2013)
Darkness had come to the town. Strange things were happening in the dead of night. Children would put a tooth under their pillow for the tooth fairy, but in the morning they would wake up to find... a dead slug; a live spider; hundreds of earwigs. Evil was at work. But who or what was behind it...?